2013
DOI: 10.1371/journal.pone.0083680
|View full text |Cite
|
Sign up to set email alerts
|

Cryogenic Transmission Electron Microscopy Nanostructural Study of Shed Microparticles

Abstract: Microparticles (MPs) are sub-micron membrane vesicles (100–1000 nm) shed from normal and pathologic cells due to stimulation or apoptosis. MPs can be found in the peripheral blood circulation of healthy individuals, whereas elevated concentrations are found in pregnancy and in a variety of diseases. Also, MPs participate in physiological processes, e.g., coagulation, inflammation, and angiogenesis. Since their clinical properties are important, we have developed a new methodology based on nano-imaging that pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
72
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 78 publications
(79 citation statements)
references
References 46 publications
6
72
1
Order By: Relevance
“…1F and 1G, revealed that many of the vesicles contained smaller vesicular structures within the lumen, which might represent cellular organelles or remnants thereof, or could be an artifact of MP preparation. The shapes, sizes, and the vesicles-within-vesicle feature of MP corresponded well with the nanostructures reported recently by Issman and Yuana (15,26), and confirmed successful isolation of MP from human plasma. We mathematically simulated the sedimentation behavior of MP and platelets (supplemental Fig.…”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…1F and 1G, revealed that many of the vesicles contained smaller vesicular structures within the lumen, which might represent cellular organelles or remnants thereof, or could be an artifact of MP preparation. The shapes, sizes, and the vesicles-within-vesicle feature of MP corresponded well with the nanostructures reported recently by Issman and Yuana (15,26), and confirmed successful isolation of MP from human plasma. We mathematically simulated the sedimentation behavior of MP and platelets (supplemental Fig.…”
Section: Resultssupporting
confidence: 88%
“…We believe that such an approach is in high demand to further the understanding of MP function in vascular biology and to enable for specific and sensitive screening of MP in biomarker discovery and diagnostics. MP have mostly been studied by FCM in clinical studies, although FCM is a technology known to have shortcomings in the detection of MP (12)(13)(14)(15). Nano-LC-MS/MS based proteomics is an unbiased and very sensitive analytical technology to establish an in-depth, quantitative protein parts list and to determine compositional changes, e.g.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations